Studi Pengaruh Aktifasi Termal terhadap Struktur Mikro dan Porositas Zeolit Alam - I Putu Putra Widia Semara; Tjokorda Gde Tirta Nindhia (Jurnal Energi Dan Manufaktur, 2010)
Zeolite is known as a material having ability as an adsorbent for metal pollutant in both liquid and gas wastes. Asinitial study in utilizing natural zeolite, and in order to be understood its possibility to control the dangerous metal pollutantfrom the liquid and gas wastes, then research regarding physical properties from the natural zeolite should be conductedfirst. The natural zeolite will be able to adsorb the metal pollutant in the waste if already be activated, and one of the methodto activate is by applying thermal activation technique or heating. The purpose of this research is to observe the change onmicrostructure to be related with porosity of natural zeolite from Sukabumi, West Java, Indonesia due to thermal activated,to be compared to one without thermal activation. The temperature variations for thermal activation namely: 100, 200, 300,400, and 500 o C with all have the same holding time 15 minutes. The microstructure then is observed by using stereo opticalmicroscope following the standard of ceramography standard. The change in microstructure then is analyzed and studied tobe related with the ability of natural zeolite to adsorb the metal pollutant